Glaserian Grounded Theory and Straussian Grounded Theory: Two Standard Qualitative Research Approaches in Social Science - Mohajan, Haradhan Kumar; Mohajan, Devajit (Journal of Economic Development, Environment and People, 2023)
Grounded theory (GT) has appeared as a popular research approach in many branches of social science that acts for the well-being of the society. It is an inductive methodology, and focuses on the discovery of theory from data. Overtimes original grounded theory of Barney Galland Glaser (1930-2022) and Anselm Leonard Strauss (1916-1996) has evolved, and two grounded theory variants: Glaserian grounded theory and Straussian grounded theory have been emerged as qualitative approaches. When a novice qualitative researcher starts data collection on grounded theory; s/he cannot identify the differences between the two approaches. In this paper some of the key differences and similarities of the two methods are illustrated. So that, a confused researcher can easily selects the desired grounded theory for his/her research version. In this study an attempt has been taken to continue the grounded theory research smoothly when the novice researchers face uncertainty during the research procedure.